Rancang Bangun Timer Pomodoro Portabel dengan ESP32 untuk Mengatasi Distraksi Digital - Kartika Amelia; M Reihan Fahlevi; Muhammad Rizqy Nopriandi; Naufal Indra Setiawan; Muhammad Adam; Adhitya Tirta Nugraha; Siti Aisyah Rhamadaini; Muhammad Angga Pratama; Abdul Rahman (MDP Student Conference, 2026)
Smartphone dependency is often a primary source of distraction that reduces students’ attention spans and productivity. Although the Pomodoro Technique is effective in maintaining focus, its implementation via mobile apps frequently triggers new interruptions due to social media notifications. This study aims to develop a portable ESP32-based Pomodoro device as a distraction-free time management solution. The research method employs a hardware prototyping approach, integrating an OLED display, physical navigation buttons, and haptic feedback for non-intrusive notifications. Test results demonstrate high timing accuracy with negligible deviation (<0.25 seconds) in standard sessions and an operational duration of up to 900 minutes using a 5000 mAh battery. By utilizing a tangible user interface, this device effectively separates productive activities from digital interference, offering a reliable and ergonomic focus management solution for students.